Assessment of occupational risk related stress at work among workers in oil and gas industry - Alias, Ayuni Nabilah; Yaakub, Norwahida; Abdul Razak, Nur Fazhilah; Naranthran, Priya (Politeknik Sultan Salahuddin Abdul Aziz Shah, 2024)
Psychosocial hazards have a significant influence on health and safety outcomes within the oil and gas industry. Occupational stress decreases safety behaviour, while mental health and fatigue are risk factors. Preventing occupational stress is critical for the health of employees. This study aims to determine the risk assessment level of occupational stress among oil and gas workers. The stratified random sampling method is a semi-quantitative method that implements data collection through a socio-demographic questionnaire and risk assessment matrices, including likelihood times severity (LXS) and following two phases Initial Risk (IR) and Residual Risk (RR). The overall prevalence of population was 41% consisting of social support, task, exposure, and recognition risk factors that influence occupational stress levels. Most workers are Malay, which represents 98.6% of the study population. The workforce is predominately married, with 97.3% of men. The overall rating of occupational stress risk rating in the evaluated area was moderate.